Influence of Concomitant Medications on the Total Clearance and the Risk for Supra-therapeutic Plasma Concentrations of Citalopram. A Population-Based Cohort Study - Wenzel-Seifert, K.; Brandl, R.; Hiemke, C.; Haen, E. (Pharmacopsychiatry, 2014)
Introduction: The main objective of this study was to investigate the influence of the use of multiple medications and other risk factors on citalopram plasma concentrations.Methods: A retrospective cohort study with a naturalistic population of 957 patients for whom routine therapeutic drug monitoring (TDM) of citalopram had been requested between 2006 and 2013 was conducted.Results: Concomitant drugs inhibiting at least 2 different CYP subtypes involved in the metabolism of citalopram decreased statistically significantly the total clearance (Clt). Compared to younger patients over 64-year-old patients had on average a 4.5 times higher risk rate of supra-therapeutic plasma concentrations. However, binary logistic regression showed that age, sex and co-medication accounted only for 26% of the inter-individual variability of citalopram plasma concentrations.Discussion: Due to pharmacokinetic interactions, citalopram plasma concentrations are often higher than expected with a given dose. Especially in geriatric and often multimorbid patients who are usually prescribed high numbers of concomitant drugs and are at higher risk for adverse drug reactions (ADR), restriction of the maximal dose of citalopram is not sufficient to prevent supra-therapeutic plasma concentrations.
Keywords: drug interactions; pharmacokinetics; selective serotonin reuptake inhibitors (SSRIs); citalopram; therapeutic drug monitoring